2020
DOI: 10.1039/d0ra06091g
|View full text |Cite
|
Sign up to set email alerts
|

Separation of iron(iii), zinc(ii) and lead(ii) from a choline chloride–ethylene glycol deep eutectic solvent by solvent extraction

Abstract: Deep eutectic solvents (DESs) were used as alternatives to the aqueous phase in solvent extraction of iron(iii), zinc(ii) and lead(ii).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…leaching with non-aqueous solvents), as more polar phases in non-aqueous solvent extraction and as non-aqueous electrolytes during electrowinning. 9,[13][14][15] Solvometallurgy with DESs or ILs is also often called "ionometallurgy". 16 The recovery of cobalt from secondary waste streams is a trending topic since cobalt is a critical raw material and is abundantly present in the cathode material of lithium-ion batteries (LIBs).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…leaching with non-aqueous solvents), as more polar phases in non-aqueous solvent extraction and as non-aqueous electrolytes during electrowinning. 9,[13][14][15] Solvometallurgy with DESs or ILs is also often called "ionometallurgy". 16 The recovery of cobalt from secondary waste streams is a trending topic since cobalt is a critical raw material and is abundantly present in the cathode material of lithium-ion batteries (LIBs).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the function of ChCl : EG (1 : 2) as lixiviant is emphasized, due to its recent ubiquity in solvometallurgy/ ionometallurgy. 9,21,22 The thermal stability of ChCl : EG (1 : 2) was studied by thermogravimetric analysis (TGA). Gas chromatography-mass spectrometry (GC-MS) was used to identify the decomposition products after heating at 180 °C for 24 hours, both in the presence and absence of LCO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, solvometallurgy is complementary to hydro-and pyro-metallurgy, and it can be applied whenever it provides economic and technical advantages. In terms of scaling up, it has been demonstrated that NASX systems can be operated smoothly in mixer-settlers, such as the Cyanex 923 and DES system for the separation of Dy(III) and Nd(III), 144 the Cyanex 923 and DES system for the separation of Fe(III) from Zn(II) and Pb(II), 148 and the Cyanex 923 and EG system for the separation of Y(III) and Eu(III). 82 Complete solvometallurgical processes (Figure 11) have not been developed, yet efforts have been made toward this end.…”
Section: Nasx In Metallurgical Flowsheetsmentioning
confidence: 99%
“…In the recent years, considerably research activities have been devoted to the recovery of lead from industrial processes residues by hydrometallurgical and solvometallurgical methods. Solvometallurgy is a new branch of extractive metallurgy that uses nonaqueous solvents instead of aqueous solutions . Much less research attention has been paid to the recovery of antimony from industrial process residue .…”
Section: Introductionmentioning
confidence: 99%